Pengaruh Pemberian Etanol Secara Akut Terhadap Memori Kerja Pada Tikus (Rattus norvegicus) - Basuki, Rochman; Anggraini, Merry Tiyas (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2015)
Effect of Acute Ethanol Administration on Working Memory in Rats (Rattus norvegicus)Background: Acute administration of ethanol can cause neurological disorders, including the prefrontal cortex (CPF) because ethanol is neurotoxic. One of the disorders is a decrease in memory function.Objectives: This study was to determine the effect of acute ethanol administration on spatial working memory in rats.Methods: This experimental study with a posttest-only-randomized control design involved 20 rats (Rattus norvegicus) which were divided into 4 groups (K, P1, P2 and P3) each of 5 animals. Groups P1, P2 and P3 respectively were given 15% intra-peritoneal ethanol at doses of 1, 2 and 3 g/kg/day for 20 days. Memory performance is measured by 8-arm radial maze with the parameter Number of Error, namely the number of type A errors divided by the number of arms entered.Result : After 20 days of ethanol administration, spatial working memory between groups was tested by Kruskal Wallis. The results showed that there was no significant difference, namely 0.070 (p>0.05).Conclusion: There is no significant relationship between spatial working memory in rats after acute administration of ethanol.Latar belakang: Pemberian etanol secara akut dapat menyebabkan gangguan neurologis, diantaranya cortex prefrontalis (CPF) karena etanol bersifat neurotoksik. Salah satu gangguannya berupa penurunan fungsi memori.Tujuan Penelitian: Penelitian ini untuk mengetahui adanya pengaruh pemberian etanol secara akut terhadap memori kerja spasial pada tikus.Metode Penelitian: Penelitian eksperimen dengan desain posttest-only-randomized control ini melibatkan 20 tikus (Rattus norvegicus) yang dibagi menjadi 4 kelompok (K, P1, P2 dan P3) masing-masing 5 ekor. Kelompok P1, P2 dan P3 secara berurutan diberikan etanol 15% intra peritoneal dengan dosis 1, 2 dan 3 g/kgbb/hr selama 20 hari. Kinerja memori diukur dengan maze radial 8 lengan dengan parameter Number of Error yaitu angka kesalahan tipe A dibagi jumlah lengan yang dimasuki.Hasil Penelitian : Setelah pemberian etanol selama 20 hari, memori kerja spasial antar kelompok diuji dengan Kruskal Wallis. Hasil tidak ada perbedaan yang bermakna, yaitu 0,070 (p>0,05).Kesimpulan: Tidak ada hubungan yang bermakna memori kerja spasial pada tikus setelah pemberian etanol secara akut.